Case Report: A patient with spinocerebellar ataxia type 31 and sporadic Creutzfeldt-Jakob disease. Issue 2 (4th March 2018) - Saito, Natsumi; Ishihara, Tomohiko; Kasuga, Kensaku; Nishida, Mana; Ishiguro, Takanobu; Nozaki, Hiroaki; Shimohata, Takayoshi; Onodera, Osamu; Nishizawa, Masatoyo
ABSTRACT: We report a Japanese patient with spinocerebellar ataxia type 31 (SCA31) and sporadic Creutzfeldt-Jakob disease (sCJD). A 52-year-old man developed progressive cognitive impairment after the appearance of cerebellar symptoms. Brain MR diffusion-weighted imaging (DWI) demonstrated a slowly expanding hyperintense lesion in the cerebral cortex. The patient was finally diagnosed as having both SCA31 and sCJD by identification of genetic mutations and by real-time quaking-induced conversion (RT-QUIC) analysis of the cerebrospinal fluid (CSF), respectively. Here, we report the clinical details of this rare combined case, with particular reference to the association between prion protein and the early onset of SCA31.